Intraperitoneal hemorrhage after cupping therapy. Issue 2 (March 2020) - Lu, Meng-Chuan; Yang, Chih-Jen; Tsai, Shih-Hung; Hung, Chih-Chieh; Chen, Sy-Jou
Introduction: Cupping therapy has been widely performed in oriental countries and considered a safety alternative to relieve pain. Here, we report a rare complication from abdominal cupping. Case presentation: A 49-year-old man presented with a 2-day history of left upper quadrant abdominal pain after cupping therapy 3 days earlier. His abdomen was soft but appeared a localized rebounding tenderness. Contrast-enhanced computed tomography of the abdomen showed intraperitoneal hemorrhage originated from the left upper quadrant of the omentum. Discussion: Several mechanisms are proposed for the development of intraperitoneal hemorrhage after cupping therapy, including the tensile stress generated by cupping that facilitates the disruption of omentum vessels, strong negative pressure generated by cupping that suppresses blood supply to the cup-applied sites causing adjacent tissue ischemia, and subsequent vascular extravasation. Treatment for intraperitoneal hemorrhage depends on clinical conditions. Stable patients can be managed conservatively, whereas surgery is reserved for those with continuous bleeding and hypovolemic shock. Conclusion: Cupping therapy complicated with omentum bleeding can present insidiously until peritoneal irritation developed by intraperitoneal hemorrhage. A comprehensive history taking and a high degree of vigilance are crucial to diagnose early patients with this rare complication.